The Issue of Intellectual and Civilizational Decadence: An Analysis of Syeikh Muhammad al-Ghazzāli’s Discourse - MOHD DAUD, NOOR AMALI (Jurnal Usuluddin, 2022)
The issue of intellectual and civilizational backwardness ‘takhalluf’ is one of the most important issues debated in the modern Islamic discourse, especially in the early twentieth centuries. What are the factors underneath the decline of the Muslim Ummah?How it affect its present conditions?, and how to resolve the problem and bring about strategic transformation to this current situation? This article attempts to investigate the issue from Muhammad al-Ghazzālī’s scholarly insight, focusing on some of main factors deliberated by al-Ghazzālī as significant factors to Muslim decline and backwardness in the intellectual and civilizational realms. Al-Ghazzālī identified two major causes of decadence, namely internal as well external factors. Al-Ghazzālī also offers his intellectual insights on remedies for the crisis towards the betterment of Muslim nations.